Classification of electronic oscilla-tors - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2018)
This paper introduces main types of electronic oscillators as devices that in general convert energy from a direct-current source to a peri-odically varying electric output. Oscillators take two general forms: First, stand-alone benchtop units designed for electronic testing and measurement and Second, circuits integrated to other devices and many electronic circuits, such as radio receivers, transmitters, sciences, music, broadcasting, medical diagnosis, computing and other devices.Â
Keywords: Amplifier; Oscillators; Resonators.